Apparent digestibility coefficients of the extruded pellet diets containing various fish meals for olive flounder, Paralichthys olivaceus. Issue 1 (December 2016) - Rahman, Md; Han, Hyon-Sob; Kim, Kang-Woong; Kim, Kyoung-Duck; Lee, Bong-Joo; Lee, Sang-Min
Abstract Apparent digestibility coefficients (ADCs) of dry matter, crude protein, crude lipid, energy, essential amino acids, and fatty acids in extruded pellets containing various fish meals were determined for olive flounder (Paralichthys olivaceus ). Eight extruded pellet diets were prepared to contain different fish meals (herring fish meal, anchovy fish meal, mackerel fish meal, sardine fish meal-A, sardine fish meal-B, tuna fish meal, pollock fish meal-A, and pollock fish meal-B) designated as HM, AM, MM, SM-A, SM-B, TM, PM-A, and PM-B, respectively. Chromic oxide (Cr2 O3 ) was used as an inert indicator at a concentration of 0.5 % in the diet. Feces were collected from triplicate groups of fish (151 ± 4.0 g) using a fecal collection column attached to the fish rearing tank for 4 weeks. Dry matter ADCs of the MM, SM-A, SM-B, and PM-A diets were higher than those of all the other dietary groups, and the lowest digestibility of dry matter was observed in the PM-B diet. Fish fed the MM, SM-A, and PM-A diets showed significantly higher ADC of protein than those fed the AM, SM-B, TM, and PM-B diets. Lipid ADC of PM-B was significantly lower than that of the other diets. Energy ADCs of fish fed the MM, SM-A, and PM-A diets were significantly higher than those of the other diets. The availability of essential amino acids in the MM, SM-A, and PM-A diets were generally higher than that of the other fish meal diets, while TM showed the lowest values among all the experimental diets. ADCs of fatty acids in the AM, MM, SM-A, and PM-A diets were generally higher than those of fatty acids in the other diets, and the lowest values were recorded for the PM-B diet. These results provide information on the bioavailability of nutrients and energy in various fish meals which can be used to properly formulate practical extruded feeds for olive flounder.